PENGARUH KECEPATAN PUTAR, KEDALAMAN PEMOTONGAN DAN LAJU PEMAKANAN TERHADAP GETARAN ARAH RADIAL PADA MESIN BUBUT CNC - Mathius Wagyantoro Resi Bagus Panuntun; F.X. Eko Arianto; Joshua B.P. Manurung (Politeknik Meta Industri, 2022)
Vibration in machine tools can be caused by many factors, one of which is the induction factor caused by cutting parameters. In this experiment, measurements of radial vibration were carried out due to spindle rotation speed, depth of cutting, and feed rate. The experiment was carried out on a Gildemeister NEF CNC lathe with S45C material using an ISO 6 Insert R16 tip ZCC-CT. Each factor has three levels and the experimental design uses a full factorial. Measurements were made using an accelerometer and the results were analyzed using ANOVA on Minitab 19. From the measurement results, it was found that the main factor causing vibration in the radial direction is the spindle rotation speed. The smallest vibration is obtained from a combination of spindle speed parameters of 795.77 rpm, depth of cut of 0.25 mm, and feed rate of 0.3 mm/rot.Keywords : vibration, radial direction, ANOVA